Z-Ligustilide Induces c-Myc-Dependent Apoptosis via Activation of ER-Stress Signaling in Hypoxic Oral Cancer Cells - Hsu, Ren-Jun; Peng, Kui-Yuan; Hsu, Wen-Lin; Chen, Yu-Tang; Liu, Dai-Wei (Frontiers in Oncology, 2022)
Z-ligustilide (or ligustilide) is found in Angelica sinensis (Oliv.) Diels and may exert potential benefits in cancer treatment. Previous research has reported that ligustilide has anti-cancer effects on several types of cancer cells. However, studies of ligustilide on oral cancer cells have not been reported, especially under hypoxic conditions. This study focuses on the molecular mechanism of ligustilide-induced apoptosis in hypoxic oral cancer cells. We found that in hypoxic TW2.6 cells, ligustilide inhibited cell migration and induced caspase-dependent apoptosis. Accumulation of c-Myc accompanied by BH3-only members suggests that ligustilide may induce c-Myc-dependent apoptosis. In addition, we reported that ligustilide has an effect on ER-stress signaling. By using inhibitors of c-Myc, IRE1α, and ER-stress inhibitors, we found that cell morphologies or cell viability were rescued to some degree. Moreover, ligustilide is able to increase the expression of γ-H2AX and enhance the occurrence of DNA damage in oral cancer cells after radiation treatment. This result suggests that ligustilide has potential as a radiation sensitizer. Altogether, we propose that ligustilide may induce c-Myc-dependent apoptosis via ER-stress signaling in hypoxic oral cancer cells.